Anatomical characteristics and phytochemical screening of Homalomena perplexa: An endemic species from Con Dao National Park, Vietnam - Truong, D H; Nguyen, N T; Trinh, N N; Dang, V S; Luu, H T; Tran-thi, T T; Nguyen-Phi, N; Van, H T (Plant Science Today, 2025)
Homalomena perplexa has been recently described as a new species in the flora of Vietnam. In this study, the micro-morphological features of the different organs of H. perplexa, including the root, leaf and rhizome were provided for the first time using the iodine green-carmine double staining method. Moreover, the phytochemical screening of H. perplexa was also conducted for the first time. Accordingly, the leaf, petiole and rhizome of the studied plant were found to contain various compounds, including coumarin, steroid, terpenoid, saponin, flavonoid, alkaloid, tannin, tannin and phenolic. In addition, the total triterpene and polyphenol contents in the rhizome extract were the highest (44.82 mg OAE/g DW and 15.51 mg GAE/g DW), followed by the petiole extract (14.02 mg OAE/g DW and 11.31 mg GAE/g DW) and the leaf extract (1.44 mg OAE/g DW and 10.97 mg GAE/g DW). Furthermore, the leaf extract possessed the highest quantitative flavonoid content (77.04 mg QE/g DW), followed by the petiole and rhizome extracts with the contents of 39.68 and 35.76 mg QE/g DW, respectively.